VD_FINDINFO HC / 2017 / 709 vom 17. August 2017 - VD Tribunal cantonal (2017)
PRÉSOMPTION, OBLIGATION D'ENTRETIEN, ENFANT, ACTION EN PATERNITÉ, MESURE PROVISIONNELLE | 262 CC, 285 CC, 303 al. 2 CPC (CH)